2024
DOI: 10.1021/acs.jafc.3c08905
|View full text |Cite
|
Sign up to set email alerts
|

Novel Potential of Rose Essential Oil as a Powerful Plant Defense Potentiator

Eiki Kaneko,
Kenji Matsui,
Ruka Nakahara
et al.

Abstract: Terpenoids, natural compounds released by plants, function to enhance plant defense. The aim of this study was to investigate the effects of terpenoid-enriched essential oils (EOs) on tomato plants. From the application of a highly diluted solution of 11 different EOs to potted tomato soil, our study showed that rose essential oil (REO), rich in β-citronellol, played a crucial role in activating defense genes in tomato leaves. As a result, leaf damage caused by herbivores, such as Spodoptera litura and Tetrany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(42 reference statements)
1
0
0
Order By: Relevance
“…Nevertheless, our research indicated that MV-HCl, a more affordable and easily produced alternative to MV, showed the highest efficacy when applied to soil in potted plants. In fact, a similar effect was observed when rose essential oil was used as a plant defense potentiator in tomatoes [20].…”
Section: Discussionsupporting
confidence: 55%
“…Nevertheless, our research indicated that MV-HCl, a more affordable and easily produced alternative to MV, showed the highest efficacy when applied to soil in potted plants. In fact, a similar effect was observed when rose essential oil was used as a plant defense potentiator in tomatoes [20].…”
Section: Discussionsupporting
confidence: 55%